Pemilihan Kepala Daerah melalui DPRD sebagai Open Legal Policy: Perspektif Pasal 18 Ayat (4) UUD NRI Tahun 1945 - Lefi Evti Handayani; Mardhatillah Suaka (CV. Utami, 2026)
This article examines regional head elections through the Regional House of Representatives as an open legal policy from the perspective of Article 18 paragraph (4) of the 1945 Constitution of the Republic of Indonesia. This issue is significant because the phrase “democratically elected” does not expressly determine whether regional heads must be elected directly by the people or may be elected through a representative institution. The debate has become increasingly relevant in light of various problems associated with direct regional head elections, including high political costs, money politics, social polarization, and the budgetary burden of election administration. This article aims to analyze the legal position of regional head elections through the Regional House of Representatives as an open legal policy, compare direct and indirect models for selecting local government heads in several countries, and formulate constitutional limits to ensure that such a model does not diminish popular sovereignty. This research employs normative legal research using conceptual, statutory, and comparative approaches. The findings show that regional head elections through the Regional House of Representatives may be positioned as an open legal policy because Article 18 paragraph (4) does not constitutionally require a direct election model. However, such policy cannot be understood as unlimited legislative freedom. Election through the Regional House of Representatives can only be justified if it is designed to be open, deliberative, transparent, accountable, free from transactional politics, and accompanied by effective oversight and dispute-resolution mechanisms.